Planar Perovskite Solar Cells: Local Structure and Stability Issues. Issue 6 (1st June 2017) - Paci, Barbara; Generosi, Amanda; Wright, Jonathan; Ferrero, Claudio; Di Carlo, Aldo; Brunetti, Francesca
Abstract : Perovskite solar cells (PSC), which are among the most promising solar energy harvesting devices, have experienced tremendous progress in power conversion efficiency over the last years. However, durability and hysteresis issues are still a major obstacle. Here, an original approach addressing the relations coupling the local structure of the device active elements with the cell performances is proposed and applied, as a case of study, to integrated planar p‐i‐n PSCs: the inner bulk and interface properties are revealed by nanoscale resolution synchrotron radiation. In particular, the effect of TiOx post‐deposition annealing on both the hysteretic behavior and enhancement of the initial efficiency of the device is addressed. Moreover, phase separation between the two perovskite phases during prolonged light soaking is evidenced. Annealing is shown to mitigate the degradation at the perovskite's buried interface and at the hole‐transporting layer interface in contact with the transparent electrode. Finally, the structural stability improvement of the annealed devices reflects a superior photovoltaic performance durability compared to the pristine device. To conclude, the ability to monitor the internal structure of PSC components provides new insights into the possibility of reducing the degradation pathways under working conditions. Abstract : Nanoscale resolution synchrotron radiation layer‐wise analysis is applied for the first time to integrated planar perovskite photovoltaic cells, revealing the device inner bulk and interface properties. The ability of monitoring the internal structure of the PSC active components fuels substantially the prospective efforts aiming to reduce the degradation pathways under working conditions.